Problems of the analysis of Chaucer's poems - Varnaitė, Irena (Literatūra, 1973)
Chaucer appears a great and highly original English national poet already in his five poems written before "The Canterbury Tales". He is still dependent on the mediaeval literary conventions: "The Book of the Duchess", "The Parliament of Fowls", "The House of Fame", and "The Legend of Good Women" have the traditional form of a dream-vision.Conventional moral categories — Pity, Cruelty, Pleasure, etc. — are personified in the poems. The allegorical figures of birds in "The Parliament of Fowls" express a critical attitude of the poet towards the contemporary society. Characters drawn in a realistic manner are already encountered in the poems; they are still very static, like the Knight in Black ("The Book of the Duchess"). Gradually they acquire depth and individuality and their actions become motivated: Troilus and Criseyde ("Troilus and Criseyde").The traditional first-person narrator is quite newly introduced: the "I" is a raconteur, a commentator, and an active dramatis persona simultaneously. Often do the poet and the narrator merge into one as in philosophical and moral judgements.Chaucer's poems as if summarise the popular genres of the high Middle Ages — an allegorical, elegiac and satirical poem, a poem-romance, a tragical narration, a legend, a lyrical verse, a love song, a roundel, an alba, a letter, etc. Lyrical songs and verses are often ingredients of an epic-dramatic narrative. A poetic and satirical drama or even something of a realistic story, i.e. new genres, are discernable.The total system of the characters and imagery point to Chaucer as a great representative of the mediaeval culture and a pioneer of the Renaissance art.
Keywords: -